A processing diagram for high-density Ti-6Al-4V by selective laser melting. Issue 9 (12th November 2018) - Wang, Yinmin (Morris); Kamath, Chandrika; Voisin, Thomas; Li, Zan
Abstract : Purpose: Density optimization is the first critical step in building additively manufactured parts with high-quality and good mechanical properties. The authors developed an approach that combines simulations and experiments to identify processing parameters for high-density Ti-6Al-4V using the laser powder-bed-fusion technique. A processing diagram based on the normalized energy density concept is constructed, illustrating an optimized processing window for high- or low-density samples. Excellent mechanical properties are obtained for Ti-6Al-4V samples built from the optimized window. Design/methodology/approach: The authors use simple, but approximate, simulations and selective experiments to design parameters for a limited set of single track experiments. The resulting melt-pool characteristics are then used to identify processing parameters for high-density pillars. A processing diagram is built and excellent mechanical properties are achieved in samples built from this window. Findings: The authors find that the laser linear input energy has a much stronger effect on the melt-pool depth than the melt-pool width. A processing diagram based on normalized energy density and normalized hatch spacing was constructed, qualitatively indicating that high-density samples are produced in a region when 1 < E* < 2. The onset of void formation and low-density samples occur as E* moves beyond a value of 2. The as-built SLM Ti-6Al-4V shows excellent mechanical performance. Originality/value: A combined approach of computer simulations and selected experiments is applied to optimize the density of Ti-6Al-4V, via laser powder-bed-fusion (L-PBF) technique. A series of high-density samples are achieved. Some special issues are identified for L-PBF processes of Ti-6Al-4V, including the powder particle sticking and part swelling issues. A processing diagram is constructed for Ti-6Al-4V, based on the normalized energy density and normalized hatch spacing concept. The diagram illustrates windows with high- and low-density samples. Good mechanical properties are achieved during tensile tests of near fully dense Ti-6Al-4V samples. These good properties are attributed to the success of density optimization processes.